(3MGTjI Ydi GddeYI GdOeTbjIs - (3CMeO GdJhfjs
(3ChdgG (B:s
(3GdMeO ddg hMOg(B... (3CeG HYO, agPg JYdjbGJ GJabJ efj Ydi GdQhVI GdHgjI aj TQM GddeYI GdOeTbjI(B...s
(3BNQgG (B:s
(3hgh aGSO dCf GdJYdjd GdePchQ TQW UMI GdbjGS Gddge EdG Cf jQGO EdMGb ZjQgGs
(3JHUQI GdYfhGf (B:s
(3MGTjI GdQhVI GdHgjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis